Environmental Chemistry in Context: A Digital Supplement on Coconut Shell Briquettes - Hairida; Erlina; Astuti, Nur Anjar (Universitas Pendidikan Mandalika, 2025)
This study aimed to assess the validity of a local-issue-based coconut shell briquette e-supplement developed for an environmental chemistry course, as well as to evaluate student responses to the material. Utilizing the Research and Development (R&D) method with the ADDIE model and a descriptive quantitative approach, the study measured both expert evaluations and learner perceptions. The e-supplement was reviewed by two content experts, two linguistic experts, and two media experts, and was tested by ten students enrolled in the Chemistry Education program at FKIP UNTAN. Data were collected through a combination of direct and indirect communication techniques, along with measurement instruments including validity assessment sheets and response questionnaires. The findings revealed that the e-supplement achieved a validity score of 81.25% in material quality, 87.50% in linguistic clarity, and 94.44% in media presentation. Additionally, student responses indicated a high level of approval, with a 91.5% positive rating. Based on these results, the e-supplement is considered suitable for implementation in environmental chemistry education, and it shows promising potential to support contextual learning and contribute to Education for Sustainable Development (ESD).